PENGARUH PERENCANAAN KARIR DAN BIAYA PENDIDIKAN TERHADAP MINAT MELANJUTKAN PENDIDIKAN PROFESI GURU (PPG) - Putra, Iwan; Yuliyanti, Ribka; Liputo, Muhammad Arif (Jurnal Pendidikan Ekonomi, 2024)
This study was conducted to determine the effect of career planning and education costs on the interest of economic education students, FKIP, Jambi University, batch 2020 and 2021 to continue teacher professional education (PPG). This study uses a quantitative method approach. This study took 175 students of the economic education study program, batch 2020 and 2021 as the population, with 122 samples. Data were collected using a questionnaire distributed online via google form. The results of the study revealed that (1) career planning has a positive and significant effect on the interest in continuing PPG, with a t-count value of 5.313 greater than the t-table value of 1.9801, (2) education costs have a negative and significant effect on the interest in continuing PPG, with a t-count value of -2.287 greater than the t-table value of 1.9801, (3) career planning and education costs have a positive and significant effect on the interest in continuing PPG, with an f-count value of 16.255 greater than the f-table value of 3.07.